1990
DOI: 10.1177/001872679004300505
|View full text |Cite
|
Sign up to set email alerts
|

Moral Reasoning in Groups: Leaders Make a Difference

Abstract: This article reviews a program of research on how groups reason about moral dilemmas, and presents data from two studies. In the first study, discussions of 21 four-member groups were tape recorded, coded, and analyzed to identify the factors that affected group performance. The data indicated that a group's moral reasoning level (as measured by Rest's Defining Issues Test) seemed to depend on whether more principled reasoning members took a task leadership role. The second study attempted to manipulate the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 22 publications
1
79
0
1
Order By: Relevance
“…Research has shown that leader initiating structure and consideration behaviors can influence the ethical frameworks (i.e., formalism and utilitarianism) observed in followers (Schminke & Wells, 1999;Schminke, Wells, Peyrefitte, & Sebora, 2002). Leaders' levels of moral reasoning can also influence their followers' moral reasoning through role modeling, observation or instruction (Dukerich, Nichols, Elm, & Vollrath, 1990). For example, when leader and follower levels of moral reasoning are congruent, research has shown that followers report higher levels of satisfaction and commitment along with lower turnover intentions (Schminke, Ambrose, & Neubaum, 2005).…”
Section: Leadership and Follower Ethical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that leader initiating structure and consideration behaviors can influence the ethical frameworks (i.e., formalism and utilitarianism) observed in followers (Schminke & Wells, 1999;Schminke, Wells, Peyrefitte, & Sebora, 2002). Leaders' levels of moral reasoning can also influence their followers' moral reasoning through role modeling, observation or instruction (Dukerich, Nichols, Elm, & Vollrath, 1990). For example, when leader and follower levels of moral reasoning are congruent, research has shown that followers report higher levels of satisfaction and commitment along with lower turnover intentions (Schminke, Ambrose, & Neubaum, 2005).…”
Section: Leadership and Follower Ethical Outcomesmentioning
confidence: 99%
“…Further, exposure to role models with higher levels of cognitive moral development (CMD; Kohlberg, 1981;Rest et al, 1999) may also promote higher CMD in observers through providing new moral perspectives (Dukerich et al, 1990). Authentic leaders with high levels of moral perspective who transparently discuss moral issues may play this role.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…There is relatively little research that investigates moral reasoning in groups, and only one of the identified articles reviewed experimental studies in this area. 151 As moral reasoning is central to the work of DMCs, the findings of this review will be described here in some detail.…”
Section: Experimental Studies Of Moral Reasoningmentioning
confidence: 99%
“…Dukerich and colleagues 151 review existing research using the DIT to investigate moral reasoning by groups, and present two experimental studies of their own. In these studies, participants (university students) were pretested using the DIT and then assigned to four-member groups.…”
Section: Experimental Studies Of Moral Reasoningmentioning
confidence: 99%
“…Fineman and Clarke, 1996;Crane, 2001) and ethical leadership literatures (e.g. Dukerich et al, 1990;Stahl, and Sully de Luque, 2014) (see Amaeshi, 2009). Furthermore, a key theme central to these is the emphasis they place on the centrality of the 'manager' in shaping firm behaviour.…”
mentioning
confidence: 99%